Calidad de servicio y satisfacción de usuarios en el departamento de pediatría del Hospital Regional de Loreto 2022 - Ruiz Pezo, Jack Werner (2025)
The general objective of the work is to determine the association between service quality and the level of user satisfaction in the Pediatrics Department of the Regional Hospital of Loreto in the year 2022. This is a quantitative study with a descriptive, analytical, cross-sectional, and correlational design. The sample included 353 participants, 56 from hospitalization and 297 from outpatient clinics, selected proportionally stratified according to the total number of users of the pediatric service, based on the 2021 population. A survey was used as a technique, and the modified SERVQUAL questionnaire was employed as the instrument. The survey was conducted with the informed consent of the participants, and the following results were obtained: Regarding the gaps in service quality across dimensions, users from both outpatient clinics and hospitalizations generally expressed dissatisfaction in empathy (65.4%), safety (64.8%), responsiveness (67.1%), reliability (61.2%), and tangibility (69.7%). Regarding the level of satisfaction in hospitalization, it was found that 88.24% of users were satisfied, and 11.76% were dissatisfied. In outpatient clinics, 57.39% of users expressed dissatisfaction, while 42.61% expressed satisfaction. It is concluded that there is a significant statistical association between the quality of care and the level of patient satisfaction, with a Pearson coefficient of 0.357 with p<0.001, indicating a moderate correlation.